Dysbiosis of Gut Microbiota and Short‐Chain Fatty Acids in Acute Ischemic Stroke and the Subsequent Risk for Poor Functional Outcomes. Issue 3 (30th May 2020) - Tan, Chuhong; Wu, Qiheng; Wang, Huidi; Gao, Xuxuan; Xu, Ruoting; Cui, Ziming; Zhu, Jiajia; Zeng, Xiuli; Zhou, Hongwei; He, Yan; Yin, Jia
Abstract: Background: The intestinal microbiota and its metabolites have been reported to play an important role in stroke. Gut microbiota–originating short‐chain fatty acids (SCFAs) modulate brain functions directly or indirectly through immune, endocrine, vagal, and other humoral pathways. However, relatively few investigations have evaluated the gut microbiome and SCFAs spectrum or their potential associations with stroke outcomes in acute ischemic stroke (AIS) patients with different stroke severities. Methods: We used 16S rRNA gene sequencing and gas chromatography to compare the fecal microbial composition and SCFA spectrum between AIS patients (n = 140) and healthy controls (n = 92). Their associations with 90‐day poor functional outcomes were evaluated by logistic regression models. Results: We found that the intestinal microbiota distinguished AIS patients from healthy controls. A lack of SCFAs‐producing bacteria and a low fecal SCFAs level defined dysbiosis in AIS patients, especially those with increased stroke severity. The SCFAs levels were negatively correlated with stroke severity and prognosis. Reduced SCFAs levels, especially acetate, were associated with an increased risk of 90‐day poor functional outcomes even after adjustments. Conclusions: Dysbiosis of SCFAs‐producing bacteria and SCFAs in AIS patients increased the subsequent risk for poor functional outcomes, indicating that SCFAs could be potential prognostic markers and therapeutic targets for stroke.